PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN TANGGUNG JAWAB DAN PRESTASI BELAJAR - Malhudin Malhudin (DIADIK, 2022)
This research was conducted with the aim to find out 1) The application of the Problem Learning can increase Responsibility student, 2) The application of the Problem Learning can improve student learning achievement in mathematics student in Class VIII in SMP Negeri 4 Kikim Selatan Kabupaten Lahat. The problem in this study is that the learning methods used are less varied, the low attitude of student obligation in learning. This study used 20 subjects in PTK research. Data collection techniques in this study used observation and tests. The results of this study indicate that  The application 0f a Problem Learning can increase student Responsibility in Mathematics subjects. The application of a Problem Learning can improve student learning achievement in Mathematics subjects class VIII in SMP Negeri 4 Kikim selatan Kabupaten Lahat.